2021
DOI: 10.3390/ani11082373
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Risk of Nodal Metastases in Canine Integumentary Mast Cell Tumors: Is Sentinel Lymph Node Biopsy Always Necessary?

Abstract: The recent literature supports the sentinel lymph node (SLN) biopsy in dogs with MCT due to discrepancy with the regional lymph node and the high percentage of occult metastasis. However, the SLN biopsy includes additional anesthesiologic, diagnostic, and surgical procedures, and additional costs. The study aimed to assess the association between clinicopathological variables and SLN status, determining the identification of dogs at lower risk of SLN metastases. Dogs with integumentary MCT were admitted to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(61 citation statements)
references
References 35 publications
6
50
2
Order By: Relevance
“…For age and weight, the median was used as the cut‐off value. For tumour diameter, a cut‐off value of 3 cm was selected based on previous studies 2,13 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For age and weight, the median was used as the cut‐off value. For tumour diameter, a cut‐off value of 3 cm was selected based on previous studies 2,13 …”
Section: Discussionmentioning
confidence: 99%
“…For tumour diameter, a cut-off value of 3 cm was selected based on previous studies. 2,13 Data were analysed by use of commercial software programs (SPSS Statistics v. 26, IBM, Somers, NY, and Prism v. 5.0, GraphPad, San Diego, CA). p Values ≤ .05 were considered significant.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Lapsley et al demonstrated in their study with cMCT and scMCT patients using ICTL to determine SLN that the SLN differed from RLN in 25% of the cases and the histopathology of the SLN altered the treatment recommendation in 50% of the examined cases, however, this pre-post study only included 17 MCT patients (96). Another study found a correlation between the size of cMCT or scMCT and a significantly higher risk to develop LN metastasis using lymphoscintigraphy SLN mapping (97). However, SLN mapping and biopsy of these LNs requires additional diagnostic and invasive procedures that are expensive and not always available, and therefore not widely used in veterinary practice.…”
Section: Lymph Node Assessmentmentioning
confidence: 99%
“…Also, the regional LN (RLN), which is the anatomically closest LN, may not be the draining sentinel LN (SLN) (91). More recently, a number of studies examined different techniques to identify SLN, including methylene blue dye, lymphoscintigraphy, indirect computed tomography lymphangiography (ICTL) and contrast enhanced ultrasound (CEUS) (91)(92)(93)(94)(95)(96)(97). For example, Lapsley et al demonstrated in their study with cMCT and scMCT patients using ICTL to determine SLN that the SLN differed from RLN in 25% of the cases and the histopathology of the SLN altered the treatment recommendation in 50% of the examined cases, however, this pre-post study only included 17 MCT patients (96).…”
Section: Lymph Node Assessmentmentioning
confidence: 99%
“…But the question of which node to sample was emphasised as clinicians predicted the lymphatic drainage incorrectly in 45.8% of MCT patients (Fournier et al 2021). Number and localisation of the first draining lymph node of a tumour, the so-called sentinel lymph node (SLN) was shown to be inconsistent and different from the expected locoregional lymph nodes in up to 60% of cases (Worley 2014, Ferrari et al 2021, Fournier et al 2021.…”
Section: Introductionmentioning
confidence: 99%